2018
DOI: 10.1186/s12889-018-5025-5
|View full text |Cite
|
Sign up to set email alerts
|

Digital Media-based Health Intervention on the promotion of Women’s physical activity: a quasi-experimental study

Abstract: BackgroundTechnological advances have caused poor mobility and lower physical activity among humankind. This study was conducted to assess the impact of a digital media-based (multi-media, internet, and mobile phone) health intervention on promotion of women’s physical activity.MethodsIn this quasi-experimental study, 360 women were divided into case and control groups. The digital media-based educational intervention was conducted in two months in the case group electronically, using mail and Internet and tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 21 publications
3
44
0
4
Order By: Relevance
“…Five papers [19][20][21][22][23] were included in the analysis. In assessing the quality of research through the risk of bias, four papers with a randomized controlled trial (RCT) research design were evaluated and one with a quasi-experimental design ( Figure 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Five papers [19][20][21][22][23] were included in the analysis. In assessing the quality of research through the risk of bias, four papers with a randomized controlled trial (RCT) research design were evaluated and one with a quasi-experimental design ( Figure 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…As a result, this physical training intervention modality may be especially practical and accessible for sedentary young females living in middle- and low-income nations, and it may help to reduce health inequities. Two recent medium- and long-term randomized controlled trials have shown that online interventions can be effective for improving physical activity behaviors for women [ 21 , 22 ]. However, to the best of our knowledge, no randomized controlled trial has been conducted to investigate the effect of an online physical training intervention on mental health and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the systematic review, quality improvement characteristics are included in 4 main areas: (1) HL is an organizational priority, (2) communication practices and standards, (3) verbal/written communication skills, and (4) patient knowledge and engagement, are commonly recommended as the main quality improvement characteristics to promote sustain HL activities and health outcome. An organization with HL priority includes a range of changes in operational planning and strategic, structures, goals, and processes facilitating quality improvements in the design of services and programs, navigation, policies, protocols, preparation of workforce, and procedures in OHL [ 53 , 54 ]. The organization makes sure that HL is integrated into all relevant planning and programs to deliver health-literate care [ 29 ].…”
Section: Discussionmentioning
confidence: 99%